Pengaruh Digitalisasi Sistem Layanan Perpajakan, Insentif Perpajakan Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Di KPP Madya Dua Jakarta Utara - Zenal Abidin; Dian Wahyudin (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
This study aims to analyze the effect of digitalization of tax service systems, tax incentives, and tax sanctions on taxpayer compliance at the Madya Dua Tax Office in North Jakarta. This study is motivated by the importance of improving tax compliance through the optimization of digital services, the provision of incentives, and the enforcement of tax sanctions. The research method used is quantitative. Data was collected through the distribution of questionnaires and direct observation of taxpayers. The population in this study consisted of 142 taxpayers, with a sample of 105 taxpayers determined using the Slovin formula. Data analysis techniques used descriptive statistics and inferential statistics, namely multiple linear regression analysis, correlation coefficient tests, and determination coefficients. The results of the study indicate that the digitalization of tax services has a significant effect on taxpayer compliance of 41.8%, with a t-value of 2.141 > t-table 1.983. Tax incentives also have a significant effect of 28.4%, with a t-value of 2.469 > t-table 1.983. Tax penalties have a significant effect of 23.9% on taxpayer compliance, with a t-value of 12.739 > t-table 1.983. Simultaneously, the three independent variables have a strong influence on taxpayer compliance with a correlation coefficient of 0.648 and a coefficient of determination of 0.420. The F-calculated value of 24.812 is greater than the F-table value of 3.09, so the regression model is considered significant. Keywords: Tax Service Digitalization; Tax Incentives; Tax Penalties; Taxpayer Compliance